ドライバレー チイキ ノ エンコ ノ エイヨウ エン ブンプ ニ ツイテ - 中谷, 周; ナカヤ, シュウ; 鳥居, 鉄也; トリイ, テツヤ; 山県, 登; ヤマガタ, ノボル; NAKAYA, Shyu; TORII, Tetsuya; YAMAGATA, Noboru (国立極地研究所, 1977)
P(論文) 1971-1972,1972-1973年の夏季2シーズンにドライバレー地域の代表的な塩湖の栄養塩類について,その分布状況を調査した.この地域の塩湖は,各湖ごとに全く異なる水質を示すが,栄養塩類もそれぞれ異なる分布を示した.とくに,これら塩湖の窒素化合物が高濃度であることが注目されたが,その起因として流入水,湖底堆積物からの供給によるものと考えられる.溶存酸素や栄養塩類の濃度分布から,これらの塩湖ではバクテリア等生物活動が活発に行われていると考えられる結果を得た. The distribution of nutrient matters in the saline lakes in the Dry Valleys was studied on the spot in the summers 1971-1972 and 1972-1973. The presence of a large amount of nitrogen compounds in the saline lakes was pointed out and their source was discussed together with the distribution pattern of the respective nitrogen compound in the lake water. Most of the nutrient matters were probably supplied by the melt water from the adjacent glaciers and by the decomposed organic matters in the bottom sediments of each lake. departmental bulletin paper